Grain yield evaluation of maize genotypes at different planting dates - Santa Bahadur B.K. (Hasanuddin University, 2021)
The genotypic yield potential of maize is influenced by planting dates. A study was conducted in Rampur, Chitwan, Nepal, in 2013/14 to determine the best planting dates for maize genotypes. Every week from April, 2013 to March, 2014, four maize genotypes viz Hybrid RML-4/RML-17, RML-32/RML-17, ACROSS-9944/ACROSS-9942, and S99TLYQ-B were planted. The maximum grain production (5565 kg/ha) was recorded in August, followed by February (5266 kg/ha), June (4475 kg/ha), and July (4255 kg/ha). The lowest yield was obtained in November planting (2572 kg/ha) followed by December planting (3019 kg/ha). During August planting, the maximum grain yields were obtained in RML-4/RML-17 (7392 kg/ha) followed by RML-32/RML17 (6606 kg/ha) and ACROSS-9944/ACROSS-9942 (5004 kg/ha). The QPM genotype S99TLYQ-B produced the highest grain yield (4198 kg/ha) in February planting. Maize grown in the winter had a larger yield potentiality than maize grown in the rainy season. This study suggests that RML-4/RML-17, RML-32/RML17, and ACROSS-9944/ACROSS-9942 should be planted in August (winter season) and S99TLYQ-B in February (spring season) for maximizing production.